1992
DOI: 10.1007/bf00197378
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical observations on the nucellar apex of Wellwitschia mirabilis and the chemical composition of the micropylar drop

Abstract: Summary.In the young ovule of Welwitschia mirabilis the nucellar apex is dome shaped and starch begins to accumulate near the female gametophyte. With the degeneration of the cells of the nucellar apex, a pollen chamber is formed, which contains the micropylar fluid. Starch storage increases considerably in the upper part of the nucellus. Pollen drop emission is not a rhythmic process, and pollination does not produce the rapid withdrawal of droplets. The micropylar drop consists almost entirely of sugars, uro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 15 publications
1
34
1
Order By: Relevance
“…Furthermore, the drop composition is not similar to guttation fluids. This has been confirmed by Carafa et al [8], who mention that the nucellus, even before it breaks down, does not appear to have much anatomically in common with secretory tissues.…”
Section: Origins Of the Ovular Secretionmentioning
confidence: 63%
See 1 more Smart Citation
“…Furthermore, the drop composition is not similar to guttation fluids. This has been confirmed by Carafa et al [8], who mention that the nucellus, even before it breaks down, does not appear to have much anatomically in common with secretory tissues.…”
Section: Origins Of the Ovular Secretionmentioning
confidence: 63%
“…In other gymnosperms, such as Welwitschia, secretion is related to nucellar breakdown, and resorption is due to evaporation [8]. Doyle and O'Leary [16] were to the first to prove that active resorption occurred in gymnosperms.…”
Section: Origins Of the Ovular Secretionmentioning
confidence: 99%
“…These tubular structures bore surface entry pointssalpinx tubules, integumental tubes, catchment funnels, tubuli, elongate micropyles-that are not homologous but represented convergent solutions for accessing deep-seated secretory fluids by longproboscid insects (Labandeira et al, 2007a;Ren et al, 2009). Shorter tubular structures would afford access to short-proboscid and other insects, similar to the pollinators and fluid feeders on modern gnetaleans (Church, 1914;van der Pijl, 1953;Bino et al, 1984a, b;Marsh, 1987;Carafa et al, 1992;Kato et al, 1995;Wetsching & Depisch, 1999).…”
Section: Plant Features Associated With Haustellate Insect Pollinatorsmentioning
confidence: 99%
“…f. (Welwitschiaceae), and Gnetum L. (Gnetaceae)-are a broad array of small, short-proboscid or nonproboscid insects, predominantly flies, moths, and wasps, but also inconspicuous beetles with mandibulate mouthparts, as well as thrips with modified punch-and-suck mouthparts. Modern insect pollinators feed on nutritionally rewarding gnetalean pollination drops (Porsch, 1910;Meeuse, 1978;Carafa et al, 1992;Kato & Inoue, 1994) and often possess short proboscises that take up surface fluids from both male and female plant organs. Many of the extinct gnetalean taxa with ovulate organ morphology similar to the three extant lineages are inferred to have been similarly pollinated by small-winged insects (Lloyd & Wells, 1992).…”
Section: Cheirolepidiaceaementioning
confidence: 99%
“…The study of ovular secretion composition began in the second half of the twentieth century (McWilliam 1958;Ziegler 1959), yet the first in-depth studies only appeared in more recent years (Owens and Blake 1984;Owens et al 1987;Séridi-Benkaddour and Chesnoy 1988;Carafa et al 1992;Xing et al 2000). Early studies reported relatively simple water-soluble compounds (e.g., sugars, amino acids and organic acids) as components of the ovular secretions (Gelbart and von Aderkas 2002).…”
Section: Introductionmentioning
confidence: 97%